-23=6r+16

Simple and best practice solution for -23=6r+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -23=6r+16 equation:


Simplifying
-23 = 6r + 16

Reorder the terms:
-23 = 16 + 6r

Solving
-23 = 16 + 6r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-6r' to each side of the equation.
-23 + -6r = 16 + 6r + -6r

Combine like terms: 6r + -6r = 0
-23 + -6r = 16 + 0
-23 + -6r = 16

Add '23' to each side of the equation.
-23 + 23 + -6r = 16 + 23

Combine like terms: -23 + 23 = 0
0 + -6r = 16 + 23
-6r = 16 + 23

Combine like terms: 16 + 23 = 39
-6r = 39

Divide each side by '-6'.
r = -6.5

Simplifying
r = -6.5

See similar equations:

| 8-6-2= | | (3x-30)(3x+3)-(2x-1)=0 | | y^2-26y+45=0 | | 8m+5=5m+15 | | 11-2x=-x-3 | | -23=6r+12 | | 18r+4= | | -23=16r-5 | | 3x^2+2x-x=0 | | 5x+3=37x | | 54=8g+10-4(3g+12) | | 2(2x+40)=180 | | 54=8g+12-4(3g+12) | | 1x+5=10x | | 12-2y=y-6+3y | | 5(9x+13)=7(4x+10) | | -35+7+12-18-1-16= | | 2(6x+14)=7(8x+12) | | 2(x+8)=5(x+11) | | 16=3x-X | | X=27+-1Y | | 6=3y+9 | | 2(x+6)=5(x+12) | | 20-/2=50 | | 1.5x=24 | | 1.5=24 | | 15=300 | | 3p^2-5p+2=y | | ln(X-7)-5=2 | | X+Y+10=37 | | 2/9t=36 | | 3B+4B=24 |

Equations solver categories